Evaluation of Antioxidant Potential of Commercial Cinnamon Samples and Its Vasculature Effects. (23rd March 2022) - Moreno, Emily K. G.; de Macêdo, Isaac Y. L.; Batista, Erica A.; Machado, Fabio B.; Santos, Gabrielle R.; Andrade, Daniela M. L.; Rocha, Matheus L.; Lima, Nerilson M.; Vaz, Boniek G.; Gil, Eric S.
Abstract : Growing concerns on free radicals are the oxidative processes associated with physiological damage. The consumption of functional foods and use of plants with antioxidant capacity are widespread. Given the importance of determining antioxidant capacity in relation to the therapeutic effect, this study was aimed at evaluating cinnamon extract ( Cinnamomum sp.) in commercial samples by spectrophotometric and voltammetric methods and assessing the vascular activity of some samples. The spectrophotometric methods performed were DPPH (1, 1-diphenyl-2-picrihydrazine), ABTS (2, 21-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)), and Folin-Ciocalteu radical sequestration assays. For the electrochemical experiments, a three-electrode system was used, consisting of carbon paste electrode, platinum wire, and Ag/AgCl/KClsat, representing the working, auxiliary, and reference electrodes, respectively. The electroanalytical methods used were differential pulse, square wave, and cyclic voltammetries. The extracts were prepared in hydroalcoholic solution. A calibration curve with gallic acid was calculated to quantify their equivalent amounts in the analyzed extract. The correlation between the electrochemical approach and the total phenols calculated by the ABTS, DPPH, and Folin-Ciocalteu methods was 0.63, 0.7, and 0.73, respectively, with 1 being an ideal directly proportional correlation. The correlation between spectrophotometric methods was 0.83. A biosensor was developed in a carbon paste electrode using the enzyme laccase, obtained by the fungus Marasmiellus colocasiae . It was observed that the antioxidant profile of the cinnamon samples had an analytical sign improvement of up to 4 times when compared with the electrode without the modification. The samples were analyzed by mass spectrometer, and the main chemical markers found were coumarin, cinnamaldehyde, and eugenol. Pharmacological trials showed that these samples also induce a significant vasorelaxant effect associated to antioxidant potential on vascular injury induced by oxidative stress. Thus, cinnamon showed a high antioxidant capacity, in agreement with the results obtained in other studies, emphasizing its importance as a functional food.